Main genetic researches developed at the Instituto de Ciencia Animal since its foundation - Fraga, Luis M. (Cuban Journal of Agricultural Science, 2016)
This paper presents the main results of the researches developed at the Instituto de Ciencia Animal from the Republic of Cuba in the field of genetics. These researches were mainly aimed to the study of those species of economical interest to the country. These species are beef and dairy cattle, buffaloes, pigs, sheep, goats, birds and rabbits. This review can be useful for designing new contributions in topics not deeply researched yet and, due to their importance, could help to achieve a more efficient animal production. Key words: genetics